Electrochemical Exfoliation of Naturally Occurring Layered Mineral Stibnite (Sb2S3) for Highly Sensitive and Fast Room‐Temperature Acetone Sensing. Issue 19 (31st May 2022) - Li, Jialong; Niu, Yue; Zeng, Junwei; Wang, Jianqiang; Wang, Quan; Liu, Xiangcheng; Li, Hao; de Rooij, Nicolaas Frans; Wang, Yao; Zhou, Guofu
Abstract: The analysis of exhaled acetone is used as a noninvasive diagnosis for diabetes. Compared with traditional breath analysis tools, chemiresistive gas sensors have attracted more attention for real‐time monitoring, owing to the possibility of integration and facile operation. However, most reported room‐temperature acetone gas sensors suffer from complicated preparation, costly raw materials, or relatively long response and recovery time. In this work, naturally occurring layered mineral stibnite is used to prepare Sb2 S3 by a one‐step method of electrochemical cathodic exfoliation. As‐prepared Sb2 S3 displays an amorphous feature with porous, hierarchical nanostructure, and its formation mechanism is rationally proposed. The porous, hierarchical and amorphous Sb2 S3 ‐based gas sensors show excellent gas sensing performance toward acetone at room temperature, with the high response up to 1.46 toward 100 ppm acetone, and fast gas response and recovery toward acetone at room temperature (7 s for response and 30 s for one response–recovery cycle), which is one of the top three shortest response times among the reported room‐temperature acetone gas sensors. The electrochemical cathodic exfoliation may offer a new strategy for facile preparation of mineral materials, and the discussed devices may hold great promise for developing cost‐effective and high‐performance acetone sensors at room temperature. Abstract : Naturally occurring layered mineral stibnite is used as raw material to prepare Sb2 S3 by a facile one‐step method of electrochemical cathodic exfoliation, which displays an amorphous feature with porous, hierarchical nanostructure. The Sb2 S3 ‐based acetone gas sensors show excellent gas sensing performance toward acetone at room temperature.